Spatial transcriptomics of progression gene signature and tumor microenvironment leading to progression in mycosis fungoides - Myoung Eun Choi; Gyeonghoon Kim; Hwa-Jeong Shin; Chong Hyun Won; Sung Eun Chang; Mi Woo Lee; Woo Jin Lee (Blood Advances)
Abstract: Mycosis fungoides (MF) is characterized by stepwise evolution from patch to plaque and sometimes to tumor. Identifying patients with early-stage MF who could progress to an advanced stage is challenging. This study investigated changes in transcriptomic expression and the tumor microenvironment associated with MF progression. Spatially resolved transcriptomic profiling was conducted using CD3, CD4, and CD30 morphology markers. In the lymphoma cell area, genes linked to collagen fibril assembly and regulation of interleukin-4 were upregulated as the disease progressed from patch- to plaque-stage MF. Genes involved in the cell cycle and glutamate catabolism were upregulated during the transition from plaque- to tumor-stage MF. Forty-six significant genes that consistently increased in expression during progression were identified. Patients with stage I MF with high-progression signatures showed significantly increased cancer-associated fibroblast (CAF; P = .008) and were more likely to progress (P < .001) and receive radiation (P = .023) during follow-up. Furthermore, M2 macrophages significantly increased in lymphoma cell areas (P < .001) and immune cell areas (P = .031) in plaque-stage MF compared with patch-stage MF. CD163 expression was significantly correlated with most of the progression signatures and T-cell exhaustion markers (lymphocyte activation gene-3, T cell immunoglobulin and mucin-domain containing-3). Immunohistochemical staining revealed that several CAF markers and CD163 significantly increased during progression, and these markers were more frequently observed in progressive stage I MF compared with indolent stage I MF. In conclusion, this study identified significant transcriptomic changes during MF progression and found that tumor microenvironment, particularly M2 macrophages and CAFs, could contribute to progression in early-stage MF.